Estándares, enseñanza de las ciencias y control político del saber. (2004)
The ideologies of neoconservatism and neoliberalism have reaffirmed their intentions of political control of knowledge. To achieve their goals they have cleveloped a series of global policies that reinstall the Taylor's perspective in educatíon ancl the tradicional viewpoints of curricula, Educational technology finds new sceneries to affect Colombian Education because of the expedition of basic standards for competences.  In the field of science teaching they reaffirm scientific and technological depenclence, obstruct the development of a national techno scíentifíc culture and reproduce the traditional models of teaching and learning.